PERFIL DOS MEDICAMENTOS UTILIZADOS POR MULHERES PÓS-MENOPAUSA DO MUNICÍPIO DE CATUÍPE/RS - Wirzbicki, Dieine C. d. M.; Colet, Christiane d. F.; Berlezi, Evelise M.; Oliveira, Karla R. d. (Salão do Conhecimento, 2013)
Resumo